2014
DOI: 10.1016/j.gie.2013.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Trends in utilization of diagnostic and therapeutic ERCP and cholecystectomy over the past 25 years: a population-based study

Abstract: Design:Retrospective, comprehensive population-based study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 24 publications
3
43
0
1
Order By: Relevance
“…This is in large part due to the fact that the predictive value of preoperative risk stratification algorithms has been disappointing; thus, some have continued to advocate for universal application of IOC during LC performed for therapy of gallstone disease 8–13. Not unexpectedly, this has led to a marked increase in the use of ERCP in the era of laparoscopic gallbladder surgery 1 3 4 14 15. Despite the almost universal adoption of ERCP as a follow-up study to abnormalities identified on IOC, the optimal evaluation of patients with abnormal IOC findings is incompletely defined.…”
Section: Discussionmentioning
confidence: 99%
“…This is in large part due to the fact that the predictive value of preoperative risk stratification algorithms has been disappointing; thus, some have continued to advocate for universal application of IOC during LC performed for therapy of gallstone disease 8–13. Not unexpectedly, this has led to a marked increase in the use of ERCP in the era of laparoscopic gallbladder surgery 1 3 4 14 15. Despite the almost universal adoption of ERCP as a follow-up study to abnormalities identified on IOC, the optimal evaluation of patients with abnormal IOC findings is incompletely defined.…”
Section: Discussionmentioning
confidence: 99%
“…(2) To emulate a case mix in clinical practice, we assumed that some individuals with symptomatic CBD stones had concomitant obstructive jaundice and cholangitis. In 2012, 23% of U.S. hospitalizations principally for CBD stones were complicated by cholangitis.…”
Section: Methodsmentioning
confidence: 99%
“…(1) ERCP is the gold standard for the management of a variety of disorders, including symptomatic common bile duct (CBD) stones, biliary cholangitis, and pancreatic and biliary malignancy. (2) Unique to ERCP is the duodenoscope, an endoscope with an elevator channel that allows for the placement of guidewires, catheters and other endoscopic accessories into the operator’s visual field. While the design of this endoscope permits technically advanced and precise biliary procedures, the difficult to access elevator channel poses a challenge for effective duodenoscope reprocessing and decontamination.…”
Section: Introductionmentioning
confidence: 99%
“…Although this is the first description of rates of BDS in the United States, a study of the single Canadian province of Manitoba also indicated a marked decrease in rates of open bile duct exploration coincident with the growth of therapeutic ERCP between 1984 and 2009. 18 …”
Section: Discussionmentioning
confidence: 99%